COMPARISON OF ORDINARY AND UNUSUAL SURFACES IN GRAPHENE SYNTHESIS - Bakirov Eldorbek Valijon ogli (Western European Studies, 2024)
Due to its electronic and mechanical properties and high chemical stability, research is being conducted on graphene growth by various methods. Among them, although CVD is one of the most effective methods, one of the main problems in graphene growing is the correct choice of the metal catalyst surface. For this reason, in this research paper, the probability of graphene growth on surfaces with a high Ni index(331) and a low Ni index (111) was estimated by the molecular dynamics (MD) method. The surface energy of the g-Ni(331) surface with graphene is higher than that of the g-Ni(111) surface, which is considered the most efficient for graphene growth (0.5 J / m2). it turned out to be lower. This means that graphene can be grown both on Ni(331) surfaces with a high index and on Ni(111) surfaces with a low index, which can be used to make nanodevices (nanotransistors, batteries, water filters, capacitors, etc.).
Keywords: Ni surfaces; chemical vapor deposition; graphene